2016
DOI: 10.7448/ias.19.1.20683
|View full text |Cite
|
Sign up to set email alerts
|

High rates of virological failure and drug resistance in perinatally HIV‐1‐infected children and adolescents receiving lifelong antiretroviral therapy in routine clinics in Togo

Abstract: IntroductionAntiretroviral treatment (ART) has been scaled up over the last decade but compared to adults, children living with HIV are less likely to receive ART. Moreover, children and adolescents are more vulnerable than adults to virological failure (VF) and emergence of drug resistance. In this study we determined virological outcome in perinatally HIV-1-infected children and adolescents receiving ART in Togo.MethodsHIV viral load (VL) testing was consecutively proposed to all children and adolescents who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 23 publications
10
62
5
1
Order By: Relevance
“…The prevalence of HIV-DRM of 90.4% in children and adolescents with virologic failure in our cohort is comparable with similar settings [9,2930] and the adult population in our clinic [31]. The multiclass resistances, present in almost 80% of all failing patients dramatically limits future treatment options and represents an important public health concern.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The prevalence of HIV-DRM of 90.4% in children and adolescents with virologic failure in our cohort is comparable with similar settings [9,2930] and the adult population in our clinic [31]. The multiclass resistances, present in almost 80% of all failing patients dramatically limits future treatment options and represents an important public health concern.…”
Section: Discussionsupporting
confidence: 72%
“…The late detection of patients with treatment failure leads to the accumulation of drug resistances and dramatically limits treatment options [9,43]. The implementation and upscaling of viral load monitoring is essential to maintain treatment options and optimize health outcomes in resource-limited settings with restricted treatment possibilities [9,10,29]. …”
Section: Discussionmentioning
confidence: 99%
“…Finalizando, cabe ainda alertar quanto a um problema que também poderá surgir devido não adesão ao tratamento medicamentoso, que é a resistência aos antirretrovirais, como já relatado em estudo com realizado com crianças e adolescentes infectados pelo HIV 22 . Quando há falha na regularidade e no horário de tomar os medicamentos, a pressão que a droga exerce sobre o vírus é diminuída favorecendo o aparecimento de mutações de resistência.…”
Section: Discussionunclassified
“…Intermittent medication adherence increases the risk of treatment failure and subsequent development of drug resistance . Studies in high‐ and low‐resource settings have shown that adolescents have worse virological outcomes than other age groups . Those with chronic conditions may be more impacted by the risk‐taking behaviours that characterize adolescence than their peers without chronic medical problems in terms of impact on their health and ability to manage their illness .…”
Section: Adolescents and Treatment Outcomesmentioning
confidence: 99%